Whole‐brain atrophy assessed by proportional‐ versus registration‐based pipelines from 3T MRI in multiple sclerosis. Issue 8 (18th July 2018) - Hemond, Christopher C.; Chu, Renxin; Tummala, Subhash; Tauhid, Shahamat; Healy, Brian C.; Bakshi, Rohit
Abstract: Background and Purpose: Whole‐brain atrophy is a standard outcome measure in multiple sclerosis (MS) clinical trials as assessed by various software tools. The effect of processing method on the validity of such data obtained from high‐resolution 3T MRI is not known. We compared two commonly used methods of quantifying whole‐brain atrophy. Methods: Three‐dimensional T1‐weighted and FLAIR images were obtained at 3T in MS ( n  = 61) and normal control (NC, n  = 30) groups. Whole‐brain atrophy was assessed by two automated pipelines: (a) SPM8 to derive brain parenchymal fraction (BPF, proportional‐based method); (b) SIENAX to derive normalized brain parenchymal volume (BPV, registration method). We assessed agreement between BPF and BPV, as well their relationship to Expanded Disability Status Scale (EDSS) score, timed 25‐foot walk (T25FW), cognition, and cerebral T2 (FLAIR) lesion volume (T2LV). Results: Brain parenchymal fraction and BPV showed only partial agreement ( r  = 0.73) in the MS group, and r  = 0.28 in NC. Both methods showed atrophy in MS versus NC (BPF p  < 0.01, BPV p  < 0.05). Within MS group comparisons, BPF ( p  < 0.05) but not BPV ( p  > 0.05) correlated with EDSS score. BPV ( p  = 0.03) but not BPF ( p  = 0.08) correlated with T25FW. Both metrics correlated with T2LV ( p  < 0.05) and cognitive subscales. BPF ( p  < 0.05) but not BPV ( p  > 0.05) showed lower brain volume in cognitively impaired ( n  = 23) versus cognitively preserved ( n  = 38) patients. However, direct comparisons of BPF and BPV sensitivities to atrophy and clinical correlations were not statistically significant. Conclusion: Whole‐brain atrophy metrics may not be interchangeable between proportional‐ and registration‐based automated pipelines from 3T MRI in patients with MS. Abstract : Determination of whole‐brain atrophy (WBA) on MRI is an important metric of disease severity in multiple sclerosis (MS). Using a cohort of persons with MS and normal controls, we compared two commonly used postprocessing pipelines to determine WBA on 3T MRI. These quantification pipelines only partially agreed and are therefore not interchangeable; we urge caution when selecting and interpreting a method for measuring WBA.